The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.epsl.2018.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic silicification of microorganisms in hydrothermal fluids

Abstract: Silica-rich hydrothermal fluids that experience freezing temperatures precipitate cryogenic opal-A (COA) within ice-bound brine channels. We investigated cryogenic silicification as a novel preservation pathway for chemo-and photo-lithotrophic Bacteria and Archaea. We find that the copartitioning of microbial cells and silica into brine channels causes microorganisms to become fossilised in COA. Rod-and coccoidal-form Bacteria and Archaea produce numerous cell casts on COA particle surfaces, while Chloroflexus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…After complete sublimation of ice this vein structure remains intact (Figures 1f and 1g). Ice‐free broken up cryogenic particles bear morphological features similar to those previously identified in terrestrial ice‐templated cryogenic opal‐A (COA), such as triple‐junctions, branched threads and sheets (Channing & Butler, 2007; Fox‐Powell et al., 2018; Figure ).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…After complete sublimation of ice this vein structure remains intact (Figures 1f and 1g). Ice‐free broken up cryogenic particles bear morphological features similar to those previously identified in terrestrial ice‐templated cryogenic opal‐A (COA), such as triple‐junctions, branched threads and sheets (Channing & Butler, 2007; Fox‐Powell et al., 2018; Figure ).…”
Section: Resultsmentioning
confidence: 55%
“…The resulting crystallization textures, expressed here at the 10 µm scale, are similar to eutectic solidification textures formed in igneous and metallic systems (Akamatsu & Plapp, 2016), thus we conclude they record the final solidification of the system at the eutectic. We also note that in pH 9 fluids, small filiform carbonates can morphologically resemble common terrestrial microorganisms (Figure 3d), with cautionary implications for interpreting potential microfossils in cryogenic particles (Fox-Powell et al, 2018).…”
Section: Direct Crystallization Versus Crystallization Upon Warmingmentioning
confidence: 87%
“…Hydrothermal activity in cold surface conditions can enhance fossil preservation (Fox-Powell, 2018). “Cryogenic opal-A” (COA) precipitates within ice-bound brine channels in Icelandic hot springs.…”
Section: Taphonomic Processesmentioning
confidence: 99%
“…The surfaces of COA particles were populated with bacterial and archaeal rods and coccoids, and particle interiors retained Chloroflexus filaments. Fox-Powell et al (2018) also detected biomolecules and inorganic microbial metabolic products in COA. The authors concluded that fossil preservation in COA is highly relevant to the exploration of extraterrestrial environments where hydrothermal activity has occurred under freezing conditions, for example on Mars and Enceladus.…”
Section: Taphonomic Processesmentioning
confidence: 99%
“…Geyserites and silica sinters could thus experience variable temperature of formation that could influence their NIR signatures. Also, some opals can form under cryogenic conditions in contact with ice grains and/or snow, like in Iceland or within the Yellowstone Park, during the winter (Channing and Butler, 2007;Jones and Renaut, 2010;Fox-powell et al, 2018). We hypothesize that some geyserites and silica sinters may exhibit CRC values consistent with continental weathering or low-temperature hydrothermal processes (below 50°C) even if formed in hydrothermal setting.…”
Section: Hydrothermal Vs Weathering Martian Hydrated Silicamentioning
confidence: 97%